Partial Response to Nivolumab and Ipilimumab in a Patient With Malignant Pleural Mesothelioma and Pre‐Existing Myasthenia Gravis Without Severe Flares or Immune‐Related Adverse Events: A Case Report - Higa, Mariko; Kuda, Tomoya; Ohya, Yuichiro; Kawasaki, Hidenori (Respirology case reports, 2025)
ABSTRACT Detailed clinical data on the combination immune checkpoint inhibitor (ICI) therapy in patients with myasthenia gravis (MG) remain limited. We report a case of malignant pleural mesothelioma with previously undiagnosed ocular MG. Owing to hepatic dysfunction, reduced doses of nivolumab and ipilimumab were administered before confirmation of anti‐acetylcholine receptor (AChR) antibody positivity. MG was diagnosed based on subtle ocular symptoms and serological tests. Prophylactic intravenous immunoglobulin and an acetylcholinesterase inhibitor were administered; combination therapy was discontinued owing to the risk of MG flare, but a partial tumour response was achieved. With disease progression, nivolumab monotherapy was reintroduced, and early steroid pulse therapy was administered owing to elevated creatine kinase, again inducing a partial response. Serological screening for anti‐AChR antibodies may help prevent severe MG flares and immune‐related adverse events. With caution, dose‐reduced and limited‐exposure ICI combination therapy may be feasible in selected patients with MG under appropriate prophylactic management. A patient with malignant pleural mesothelioma and pre‐existing myasthenia gravis (MG) was treated with reduced‐dose nivolumab plus ipilimumab, followed by reintroduction of nivolumab. Both treatment phases resulted in a partial response without severe MG exacerbations or immune‐related adverse events. This rare case emphasises the potential feasibility of immune checkpoint inhibitor (ICI) therapy in patients with MG.